Connecting measures and patterns in coconut palm planting in Mexico (2022)
Research’s goal is to identify and connect measurements and patterns in coconut palm planting types constructed by a Mexican farmer. The study was theoretically based on Ethnomathematics and was developed under a qualitative-ethnographic methodology in three stages: first, a participant observation was carried out to achieve familiarization with the peasant. Second, to collect the data, semi-structured interviews were implemented, and third, an ethnomathematical thematic analysis of the data was followed. The results show that the farmer builds two sowing systems (real frame and three bobbins) using non-conventional measures such as step and string, and, as a conventional unit of measurement, the meter. In addition, he applied trigonometric ratios and the Pythagorean theorem to find the height of the triangle, used in the triangular planting system, and implement it as a measurement standard. This work has mathematical potential for the teaching and learning of mathematical topics connected to the sociocultural context of students and teachers.